Analysis of the Effect of Profit Accounting, Economic Growth, Interest Rates and Capital Structure on Share Prices in Property and Real Estate Companies - Eka Sariningsih; Yuliana Yuliana; Iing Lukman; Nena Hayati (Komunitas Dosen Indonesia, 2024)
Economic growth signifies a period marked by an increase in real national income or real gross national product. This study aims to assess the effects of accounting profits, economic growth, interest rates, and capital structure on share prices within the financial statements of property and real estate firms listed on the Indonesia Stock Exchange. Utilizing secondary data, the sample comprises 11 property and real estate firms listed on the Indonesia Stock Exchange over a five-year period. Employing purposive sampling, the research period spans five years. Multiple regression analysis is employed as the analytical method. The findings reveal a positive correlation between capital structure and accounting profits with stock prices, whereas economic growth and interest rates do not significantly influence stock prices. This research underscores the importance for companies to prioritize factors influencing stock prices